Tunable diode laser measurements of methane fluxes from an irrigated rice paddy field in the Philippines - Simpson, I.J.; Thurtell, G.W.; Kidd, G.E.; Lin, M.; Demetriades-Shah, T.H.; Flitcroft, I.D.; Kanemasu, E.T.; Nie, D.; Bronson, K.F.; Neue, H.U. (American Geophysical Union, 1995)
This paper presents the first micrometeorological‐based measurements of methane (CH4) emissions from Asian rice paddies of which we are aware. The research features the tunable diode laser trace gas analyzer system (TGAS) recently developed at the University of Guelph. CH4 fluxes were measured between March 9 and 24, 1992, from an irrigated rice paddy field at the International Rice Research Institute (IRRI), the Philippines. The daytime CH4 flux averaged 6.0 μg m−2 s−1. The CH4 fluxes displayed a diurnal trend similar to daily soil temperature curves, with peak emissions of about 8 μg m−2 s−1 in the early afternoon. A tenfold increase in CH4 emissions (to about 70μg m−2 s−1) during a brief weeding experiment resulted from soil disturbance. Up to 25 μg m−2 s−1 of CH4 were released during a drying of the field, after which unsuitable soil redox potentials apparently suppressed methanogenesis. The CH4 flux was also arrested when the field was flooded with oxygen‐rich water during a heavy rainstorm.